<em>Answer and the Step-by-step explanation : -</em>
<em />
<em><u>1) x(y - 5) = 2</u></em>
<em />
<em>First you gotta open the brackets so then you'll get : -</em>
<em>xy - 5x = 2</em>
<em><u>Answer</u></em><em> : - " since xy is remaining the equation will not linear "</em>
<em />
<em><u>2) y - 2(x + 9) = 0</u></em>
<em><u></u></em>
<em> "y - 2x - 18 = 0 "</em>
<em> "Y = 2x + 18 "</em>
<em />
<em><u>Answer</u></em><em> : - "This is linear"</em>
<em />
<em><u>3) 3y + 6(2 - x) = 5</u></em>
<em />
<em>3y + 12 - 6x = 5</em>
<em />
<em>3y = 5 - 12 + 6x</em>
<em />
<em>3y = 6x - 7</em>
<em />
<em>Y = 2x - 7/3</em>
<em />
<em><u>Answer</u></em><em> : -This is linear </em>
<em />
<u><em>4) 2(y + x) = 0</em></u>
<em />
<em>2y + 2x = 0</em>
<em />
<em>2y = - 2x</em>
<em />
<em>y = - x</em>
<em />
<em><u>Answer</u></em><em> : - " This is linear "</em>
<em />
<em />